Mpox unveiled: Global epidemiology, treatment advances, and prevention strategies - Anna Bogacka; Agnieszka Wroczynska; Weronika Rymer; Paweł Grzesiowski; Ravi Kant; Maciej Grzybek; Miłosz Parczewski (One Health)
Mpox (monkeypox), caused by the monkeypox virus (MPXV), is a zoonotic disease from the Poxviridae family, closely related to smallpox. It presents with high fever, rash, and pustules, with human-to-human transmission first reported in the Democratic Republic of Congo in 1970. Historically, such transmissions were rare, but since 2022, an alarming global surge in infections began, originating in the United Kingdom. By mid-2024, 99,176 cases and 208 deaths were reported in 116 countries, prompting the World Health Organization (WHO) to declare Mpox a Public Health Emergency of International Concern (PHEIC) twice, in 2022 and 2024. Although vaccines for smallpox have shown partial efficacy against MPOX, viral transmission persists, and there is no specific therapy or vaccine developed solely for Mpox. Current treatments rely on therapies designed for smallpox, including antivirals like tecovirimat, brincidofovir, and cidofovir.The aim of this review is to provide an updated overview of the epidemiology, clinical presentation, and management strategies of MPOX. We discuss recent progress in diagnosis, treatment, and vaccine development while addressing key prevention strategies. Mpox risk remains high in regions like the Democratic Republic of Congo, moderate in other African countries, and lower globally, particularly among men who have sex with men (MSM), where sexual transmission predominates. Diagnosis is based on clinical presentation, confirmed by PCR testing of skin lesions or swabs, while HIV testing is recommended for adults with Mpox. Preventive measures, including isolation and the use of personal protective equipment (PPE), are essential, alongside the use of two available vaccines, Jynneos and ACAM2000, which show partial efficacy against Mpox.